Preoperative breast MRI for invasive ductal carcinoma with or without a DCIS component at needle biopsy: influence on surgical outcomes in the MIPA study - Cozzi, Andrea; Di Leo, Giovanni; Houssami, Nehmat; Gilbert, Fiona J.; Helbich, Thomas H.; Álvarez Benito, Marina; Balleyguier, Corinne; Bazzocchi, Massimo; Bult, Peter; Calabrese, Massimo; Camps Herrero, Julia; Cartia, Francesco; et al. (European Radiology, 2025)
Objectives: To analyse the impact of preoperative breast MRI on surgical outcomes of patients diagnosed with pure invasive ductal carcinoma (IDC) or IDC with an associated in situ component (IDC + ductal carcinoma in situ [DCIS]) at needle biopsy. Methods: Patients aged 18–80 years referred for upfront surgery after a diagnosis of pure IDC or IDC + DCIS at needle biopsy were retrieved from the Multicenter International Prospective Analysis (MIPA) database. In each subgroup, patients who underwent preoperative MRI (MRI groups) were matched 1:1 to those who did not (noMRI groups) according to eight confounding covariates. Surgical outcomes were compared with non-parametric statistics after calculating odds ratios (ORs). Results: Among 1051 patients with IDC + DCIS, 510 were retained after matching (255 in each group): in comparison to the noMRI group, the MRI group had significantly higher rates of first-line mastectomy (13.3% vs 6.3%; OR 2.30, p = 0.011) and of overall mastectomy (14.5% vs 7.5%; OR 2.11, p = 0.016), without significantly lowering the reoperation rate (9.4% vs 10.6%, OR 0.88, p = 0.768). Among 2459 patients with pure IDC, 1638 were retained after matching (819 in each group): the first-line mastectomy rate was not significantly higher in the MRI group (12.9% vs 12.1% in the noMRI group; OR 1.08, p = 0.654). Instead, the reoperation rate was significantly lower (2.6% vs 7.9%; OR 3.28 for avoiding reoperation, p < 0.001) with no increase in overall mastectomies (13.6% vs 13.7%: OR 0.99, p = 1.000). Conclusions: In patients with IDC + DCIS, preoperative MRI did not reduce reoperations and increased mastectomies. Conversely, in patients with pure IDC, preoperative MRI reduced reoperations without increasing mastectomies. Key Points: Question The impact of preoperative breast MRI on surgical outcomes of patients with IDC at needle biopsy is controversial and lacks large-scale investigations. Findings For pure IDC at needle biopsy, MRI reduced reoperations without increasing mastectomies; for IDC + DCIS, MRI did not reduce reoperations and increased mastectomies. Clinical relevance In patients with IDC at needle biopsy, the decision to perform preoperative breast MRI should take into account the presence of associated DCIS, as the benefits of MRI on surgical outcomes were observed only in patients with pure IDC.
CRIS-Team Scopus Importer:2025-05-09
Keywords: Breast neoplasms; Magnetic resonance imaging; Mastectomy; Mastectomy (segmental); Reoperation